ANALYSIS OF AERODYNAMIC LOAD ON FATIGUE STRENGTH OF THE HIGH-SPEED TRAIN CAR BODY - SONG Ye; WU PingBo; JIA Lu (Jixie qiangdu)
According to the actual circumstance of high-speed train in line operation four aerodynamic load cases are set up: pneumatic passing each other open wire,single train passing through tunnel,two trains passing by in tunnel and cross wind.Four types of aerodynamic load condition will be applied to the numerical finite element model of high-speed train car body. Then carry the fatigue strength of aerodynamic load analysis on the finite element model. The calculation data show that all maximum stress results under the four working conditions are less than the allowable stress of car body materials,the maximal displacement deformation occurred in the bottom of the car body. In the fatigue strength analysis,not only the vertical and lateral and aerodynamic loads combination is considered,but also a combination of longitudinal and aerodynamic loads is taken into accounted. According to the results of the fatigue assessment that a minimum safety margin is 2. 93 MPa,a minimum safety factor is 1. 083. Based on the results of the fatigue analysis that: car body structure meets the requirements of fatigue strength under the aerodynamic loads. The harsh conditions which are carried by car body at the same time are aerodynamic load and vertical load.